Maturity size and fecundity of hybrid tilapia Oreochromis aureus X Oreochromis niloticus (Perciformes: Cichlidae) from the reservoir Fernando Hiriart Balderrama “Zimapan”, Hidalgo, Mexico (UNED Research Journal, 2014)
Maturity size and fecundity of hybrid tilapia Oreochromis aureus X Oreochromis niloticus. (Pisces: Cichlidae) from the reservoir Fernando Hiriart Balderrama “Zimapan”, Hidalgo, Mexico were determined in organisms caught between 2007 and 2008. A total of 506 hybrid fishes were captured and showed a range of sizes from 20 to 28,9 cm standard length (SL), and total weight of 200 to 750g (Tw).  The estimated maturation size for females was 20,8cm and 22cm for males, respectively. Fecundity was estimated on 50 gonads and a mean of 3 113±1 826 eggs was recorded per gravid female. Based on these results, these fishes are suitable for commercial exploitation and imply good conservation in correlation to the regulatory strategies for fisheries established in the area, at least from a reproductive point of view.
Keywords: sexual ratio; hybrid; fecundity; gonadic maturity; condition factor